Surface-enhanced spectroscopy technology based on metamaterials - Dongxiao Li; Xueyuan Wu; Ziwei Chen; Tao Liu; Xiaojing Mu (Microsystems & Nanoengineering)
Abstract Surface-enhanced spectroscopy technology based on metamaterials has flourished in recent years, and the use of artificially designed subwavelength structures can effectively regulate light waves and electromagnetic fields, making it a valuable platform for sensing applications. With the continuous improvement of theory, several effective universal modes of metamaterials have gradually formed, including localized surface plasmon resonance (LSPR), Mie resonance, bound states in the continuum (BIC), and Fano resonance. This review begins by summarizing these core resonance mechanisms, followed by a comprehensive overview of six main surface-enhanced spectroscopy techniques across the electromagnetic spectrum: surface-enhanced fluorescence (SEF), surface-enhanced Raman scattering (SERS), surface-enhanced infrared absorption (SEIRA), terahertz (THz) sensing, refractive index (RI) sensing, and chiral sensing. These techniques cover a wide spectral range and address various optical characteristics, enabling the detection of molecular fingerprints, structural chirality, and refractive index changes. Additionally, this review summarized the combined use of different enhanced spectra, the integration with other advanced technologies, and the status of miniaturized metamaterial systems. Finally, we assess current challenges and future directions. Looking to the future, we anticipate that metamaterial-based surface-enhanced spectroscopy will play a transformative role in real-time, on-site detection across scientific, environmental, and biomedical fields.